REPRESENTASI MASKULINITAS PADA KARAKTER PEREMPUAN DALAM FILM “KARTINI” KARYA HANUNG BRAMANTYO - Febriani Dillawati; Muhammad Bayu Widagdo; Amida Yusriana (Interaksi Online, 2023)
Gender is an interesting topic to research to date, especially issues related to women. Patriarchal culture is often associated with problems where women are considered to only have feminine characteristics and men have masculine characteristics. In this way, women's positions are often subordinated and have low roles, functions and positions. Although in general, masculine is a label given to men, masculine can also be addressed to women who have personalities and behave like men's traits. Women can be masculine not in the context of sex but in the context of gender. This study aims to determine the representation of masculinity in female characters in the film "Kartini" by Hanung Bramantyo. The main theory used in this study is The Feminist Transmission Model. This study applies descriptive qualitative research with data collection techniques by observation and documentation where the process of taking it is by taking pictures in the film Kartini. the data analysis technique used is Roland Barthes's semiotic analysis method because by using this analysis theory, research can be interpreted in terms of meaning, namely by denotation, connotation, and also mythical meaning. Based on the findings, the Kartini film tries to provide a different alternative, because the Kartini film shows women as the main character and as a hero. Through the film Kartini, an alternative representation emerges, namely female masculinity. The masculinity of women can be seen through masculine performance which includes power, courage, heroism, leadership.